(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Observation of the developmental stage of the teacher’s communication with children showed the unity of all its features in the early stages of reflection formation and their independent functioning in the later stages. According to S.V. Kondrateva, all types and forms of reflection are activated by the pedagogue during his attempts to observe and analyze his own behavior and children’s behavior.